USING TWO TIME SCALES OF TURBULENCE FOR BOUNDARY LAYER FLOWS - Nawaf H. Saeid (Universitas Gadjah Mada, 2002)
A near wall improvement of the k-? model of turbulence is proposed and evaluated. The present model takes into account the asymptotic behavior of turbulent scales near wall region and for free turbulence region. The Kolmogorov turbulent time scale is introduced as a lower limit. The model is used for prediction of turbulent boundary layer flows. Predictions compared with experimental data of several flow cases, with encouraging results.